Two new species of Curcuma subgenus Ecomata (Zingiberaceae: Zingibereae), from Central and Southwestern Thailand - PIYAPORN SAENSOUK; THAWATPHONG BOONMA; SARAYUT RAKARCHA; CHARAN MAKNOI; MATHEE WONGNAK; SURAPON SAENSOUK (Society for Indonesian Biodiversity, 2022)
Abstract. Saensouk P, Boonma T, Rakarcha S, Maknoi C, Wongnak M, Saensouk S. 2022. Two new species of Curcuma subgenus Ecomata (Zingiberaceae: Zingibereae), from Central and Southwestern Thailand. Biodiversitas 23: 4578-4588. Two new species of Curcuma L. are described. The first species, Curcuma suphanensis P. Saensouk, Boonma, Rakarcha, Maknoi, Wongnak & S. Saensouk sp. nov. was found in Suphan Buri province, Central Thailand, and the second species namely C. rosea P. Saensouk, S. Saensouk & Boonma sp. nov. was found in Uthai Thani province, Southwestern Thailand. Both species fall into the subgenus Ecomata because of the lack of conspicuous coma bract, and the presence of epigynous glands. This brings the number of species in this subgenus worldwide to 37 species. Living specimens and spirit specimens of both new species were collected from their natural habitats, morphological attributes measured, and compared to all existing species. Neither species match any previously-described species, therefore, both of them are new species to science. The first was named Curcuma suphanensis based on its province of origin (Suphan Buri Province), and the second species was named Curcuma rosea, on account of its pinkish bracts. Morphological descriptions along with their illustrations, notes on their ecology, etymology, and distributions, are presented along with a revised key to species of Curcuma subgenus Ecomata worldwide to facilitate identification.